2021
DOI: 10.1111/crj.13457
|View full text |Cite
|
Sign up to set email alerts
|

Serum tumor necrosis factor‐α, interleukin‐1β, interleukin‐6, and interleukin‐17 relate to anxiety and depression risks to some extent in non‐small cell lung cancer survivor

Abstract: Introduction: Inflammatory cytokines are proposed as modulators for the pathogenesis of anxiety and depression (anxiety/depression), and anxiety/ depression are frequently existed in non-small cell lung cancer (NSCLC) survivors. However, no published study has explored the association of inflammation cytokines with anxiety/depression in NSCLC survivors. Objectives: We aimed to evaluate serum tumor necrosis factor-α (TNF-α), interleukin-1 beta (IL-1β), interleukin-6 (IL-6), interleukin-17 (IL-17) levels, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Twelve studies were in the survivorship setting with 9 studies involving patients with breast cancer, [46][47][48][49][50][51][52][53][54] in addition to other studies of testicular, hepatobiliary, and nonsmall cell lung cancers. 23,55,56 Seven of 12 studies (58%)…”
Section: Survivorshipmentioning
confidence: 99%
“…Twelve studies were in the survivorship setting with 9 studies involving patients with breast cancer, [46][47][48][49][50][51][52][53][54] in addition to other studies of testicular, hepatobiliary, and nonsmall cell lung cancers. 23,55,56 Seven of 12 studies (58%)…”
Section: Survivorshipmentioning
confidence: 99%
“…Regarding cognitive impairment, a study claims that increases in Th17 and interleukin (IL)-17A reduces nitric oxide production, thereby facilitating cognitive dysfunction in mice fed with excess dietary salt (15). Clinically, the relationship between Th-cell-secreted cytokines and anxiety, depression, and cognitive impairment in cancer patients has also been revealed by several previous studies (17,18). For instance, elevated tumor necrosis factor-α and IL-17 indicate enhanced anxiety and depression risks in non-small cell lung cancer (NSCLC) patients (17).…”
Section: Introductionmentioning
confidence: 73%
“…Clinically, the relationship between Th-cell-secreted cytokines and anxiety, depression, and cognitive impairment in cancer patients has also been revealed by several previous studies (17,18). For instance, elevated tumor necrosis factor-α and IL-17 indicate enhanced anxiety and depression risks in non-small cell lung cancer (NSCLC) patients (17). Moreover, IL-4 is increased in breast cancer patients with cognitive impairment (18).…”
Section: Introductionmentioning
confidence: 73%
“…The abnormal differentiation of T cells plays a crucial clinical role in anxiety and depression by dysregulating the immune system 11–15 . For instance, the T‐helper 1 (Th1)/Th2 cells ratio is elevated in people with depression 13 ; moreover, it also has been reported that Th17 cells are increased in people with depression 16 ; furthermore, another interesting study also presents that Th17 cell‐secreted cytokine (interleukin‐17 [IL‐17]) are positively correlated with the severity of anxiety and depression among lung cancer survivors 15 . Notably, accumulating studies have shown that Th1, Th2, and Th17 cells are abnormally regulated during the postpartum period 17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15] For instance, the T-helper 1 (Th1)/Th2 cells ratio is elevated in people with depression 13 ; moreover, it also has been reported that Th17 cells are increased in people with depression 16 ; furthermore, another interesting study also presents that Th17 cell-secreted cytokine (interleukin-17 ) are positively correlated with the severity of anxiety and depression among lung cancer survivors. 15 Notably, accumulating studies have shown that Th1, Th2, and Th17 cells are abnormally regulated during the postpartum period. 17,18 Taken together, we deduced that Th1, Th2, and Th17 might play an important clinical role in PPD and PPA, while related information is scarce.…”
mentioning
confidence: 99%